Ethical Concepts and the Discussion of Forensic Expertise in Turkey - Gülmen, Mete; Çekin, Necmi; Hilal, Ahmet; Alper, Benhan; Salaçin, Serpil (The Bulletin of Legal Medicine, 1998)
A medical practitioner evaluates or handles most of the cases of forensic interest in Turkey those including the forensic autopsies according to the Act number 79 of the Criminal Code Law. However in the western communities, it is illegal attempt to perform autopsy or handle a forensic case by a non-expert ( Forensic Pathologist, Legal Medicine Specialist etc..). Forensic Sciences are extremely wide interdisciplinary studies. A forensic medicine specialist or pathologist or a psychiatrist sometimes may not be sufficient in an expertise report and so that various sciences involve in answering the risen questions. We believe that the ethical concepts should be in consideration in the clinical forensic cases. Patient rights, the rights of the people in charge of responsibility of an injury or death should be in consideration as well as the deceased. So who should be an expert and how the expertise should be performed in consideration of law and ethics, are of interest in the daily forensic expertise. It will be discussed in means of ethical concepts and the former studies. Key Words: Patient Rights, Autopsy, Ethics, Forensic Medicine, Pathology.